The Use of Swear Words in an Influencer Doctor Health Communication: A Case Study of dr. Tirta - Ihza Amelia Alim; Reynaldi Firmansyah Caesar; Ika Nurhayani (Deskripsi Bahasa, 2026)
This study examines how dr. Tirta, a prominent Indonesian doctor-influencer, uses swear words and what these expressions do in his communication. As social media continues to blur the line between formal expertise and casual interaction, professionals are increasingly adopting styles that would once have seemed out of place. This shift has given rise to “professional influencers” who connect with audiences in more direct and unconventional ways. Focusing on this phenomenon, the study explores swearing not as a lapse in professionalism but as a deliberate communicative strategy. The data consist of spoken utterances collected from videos on dr. Tirta’s YouTube channel that was published in May 2025. These were transcribed and analyzed using the qualitative framework of Miles, Huberman, and Saldaña (2014), alongside Andersson and Trudgill’s sociolinguistic model of taboo language. The findings show that dr. Tirta employs swear words across a range of pragmatic functions. Expletive uses express spontaneous emotion, lending his speech a sense of immediacy and sincerity. Abusive forms, such as ‘cangkemmu’ (a coarse term for “mouth”), work less as outright insults and more as a way of flattening social distance. Most notably, the social function dominates, Javanese slang and profanity, are used to build rapport, signal shared identity, and generate what can be understood as covert prestige. Taking together, these patterns suggest that swearing, in this context, is not careless or incidental. It is a calculated stylistic choice that helps shape an approachable, credible, and distinctly modern form of professional communication.